Seasonal and diurnal variations of wet scintillation in tropical region Malaysia - Ibtihal Fawzi El-Shami; Jafri Din; Ali I. Elgayar; Ahlaam Miftah Saed (Institute of Advanced Engineering and Science, 2026)
This paper investigates the seasonal and diurnal variations of wet tropospheric scintillation in a tropical region to support the design and optimization of fade margin in satellite communication systems. A one-year Ku-band propagation measurement campaign was conducted in Johor Bahru, Malaysia, using a direct broadcast receiver (DBR) and an automatic weather station (AWS) to capture both signal and meteorological data. A comprehensive signal processing technique was applied to separate scintillation effects from rain attenuation, enabling accurate statistical characterization. The analysis was performed based on monsoon seasons and different time intervals of the day. The results indicate that higher scintillation fades are most likely to occur during the afternoon period, particularly between 3:00 pm and 6:00 pm. In addition, the inter-monsoon season exhibits a higher rate of variation in scintillation intensity due to increased convective activity, whereas the southwest monsoon shows relatively lower variability under drier conditions. The findings also demonstrate that diurnal scintillation behavior is strongly influenced by seasonal patterns, with peak intensity typically observed in the late afternoon across different monsoon periods. Unlike many existing models developed for temperate regions, this study provides experimental insights into scintillation characteristics under equatorial climatic conditions. These results offer valuable guidelines for system designers to improve fade margin allocation and enhance the reliability of satellite links in tropical environments.